On the sensitivity of PROMs during breast radiotherapy. (March 2023) - Heilemann, Gerd; Renner, Andreas; Kauer-Dorner, Daniela; Konrad, Stefan; Simek, Inga-Malin; Georg, Dietmar; Widder, Joachim
Highlights: PROMs are very sensitive in detecting treatment induced side effects in radiotherapy of breast cancer. Sensitivity simulation allows to predict trends between two cohorts when analyzing patients in a real-world setting. Framework could be used for rapid learning to determine runtime of learning cycles in evidence generating learning healthcare system. Patients reported significantly more side effects after receiving a boost of 10 Gy. Abstract: Purpose: To investigate the sensitivity of patient-reported outcome measures (PROMs) to detect treatment-related side effects in patients with breast cancer undergoing external beam photon radiotherapy. Methods: As part of daily clinical care, an in-house developed PROM tool was used to assess side effects in patients during a) whole-breast irradiation (WBI) to 40 Gy, b) WBI with a sequential boost of 10 Gy, and c) partial-breast irradiation (PBI) to 40 Gy. Results: 414 patients participated in this prospective study between October 2020 and January 2022, with 128 patients (31 %) receiving WBI, 241 (58 %) receiving WBI followed by a sequential boost, and 50 patients (12 %) receiving PBI. Significant differences in the reported toxicities (itching, radiation skin reaction, skin darkening, and tenderness and swelling) were reported between the WBI cohorts with and without boost (p < 0.001, p < 0.001, p < 0.001, and p = 0.002, respectively). The comparison of PBI with WBI (no-boost) yielded significant differences for radiation skin reaction (p < 0.001). Conclusion: The results highlight the high sensitivity of PROMs to detect treatment-related side effects in patients with breast cancer. Thus, PROMs may be a valuable tool for quality control and may support evidence-based learning from real-world data originating from daily routine care.